2014
DOI: 10.1080/00220388.2014.887687
|View full text |Cite
|
Sign up to set email alerts
|

Credit Constraints and Agricultural Productivity: Evidence from rural Rwanda

Abstract: While potentially negative impacts of credit constraints on economic development have long been discussed conceptually, empirical evidence for Africa remains limited. We use a direct elicitation approach on a national sample of Rwandan rural households to empirically assess the extent and nature of credit rationing in the semi-formal sector and its impact, using an endogenous switching model. Elimination of all constraints could increase output by some 17 per cent. Implications for policy and research are spel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
72
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 26 publications
13
72
0
3
Order By: Relevance
“…Thus, rural households with higher levels of education are less likely to suffer from credit constraints. This negative impact of education level on the probability of credit constraint was also found by Akram and Hussain [37] in their study of rural households in 16 districts of Pakistan and by Ali, Deininger [36] in Rwanda.…”
Section: Factors Affecting Credit Constraint From Formal Credit Sourcessupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, rural households with higher levels of education are less likely to suffer from credit constraints. This negative impact of education level on the probability of credit constraint was also found by Akram and Hussain [37] in their study of rural households in 16 districts of Pakistan and by Ali, Deininger [36] in Rwanda.…”
Section: Factors Affecting Credit Constraint From Formal Credit Sourcessupporting
confidence: 74%
“…More highly educated rural households generally have a greater ability to create wealth [12,31]. It is also assumed that they allocate credit more efficiently [7,36]. Thus, rural households with higher levels of education are less likely to suffer from credit constraints.…”
Section: Factors Affecting Credit Constraint From Formal Credit Sourcesmentioning
confidence: 99%
“…Recent research shows that 78%ofthe coffee farmers were constrained to access credit services while 52% were excluded from financial services all together. The lack of collateral to offer has discouraged smallholder farmers from accessing credit (Ali, Deininger, & Duponchel, 2014).Different authors such as Malimba and Ganesan (2010) have raised the problem of repayment behavior in Credit and Savings Cooperative Societies and Financial Services Consumption Constraints in Rwanda, but none has discussed about determinants of credit accessibility to smallholder farmers. This study identified and filled in the gap on the institutional factors influencing credit accessibility among smallholder coffee farmers in Gisagara District, Rwanda.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier, there is substantial evidence that income risks deter poor farmers from adopting higher-return, but riskier, crops or technologies. There is also evidence that income risks may act as significant barriers for poor households to enter high-return, high-risk nonagricultural activities (Ali et. al.…”
Section: Resultsmentioning
confidence: 99%